SQUAMOUS CELL CARCINOMA (MARJOLIN’S ULCER) SECONDARY TO HANSEN DISEASE - Muñoz, Andrés Maurício López; Guimarães, Mariana Gardone; Nery, José Augusto da Costa (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Marjolin ́s ulcer has been described as a malignant transformation arising on chronic lesions or old scars. Some authors have considered inappropriate the use of the term Marjolin’s ulcer because the French physician descri- bed the sources of ulcers, rather than tumor. Patients with Hansen disease often have neurological sequelaes, which may predispose to the development of chronic cutaneous wounds. In strange cases, these lesions could progress to squamous cell carcinoma, sometimes of the verru- cous type, having more aggressive evolution. We report a case of patient with Hansen disease, having neurological sequelae and chronic ulcer in right calcaneus region that after many years it presented malignant transformation with rapid evolution, defining a clinical picture as a Marjolin’s ulcer, having been treating with amputation of rigth inferior member. KEYWORDS – Carcinoma, squamous cell; Leprosy; Skin neoplasms.